The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/20101058221111664
|View full text |Cite
|
Sign up to set email alerts
|

Subjective sleep quality among hospitalised adult patients: An observational, cross-sectional study

Abstract: Background Inpatient sleep quality is influenced by multiple factors including medical conditions, use of medication and the ward environment. Without adequate rest, detrimental effects on patients’ physical and psychological performances may persist, inhibiting recovery and increasing length of stay. Objective This study examined the sleep quality of adult inpatients and its’ associations with sociodemographic, clinical and environmental factors. Methods An observational study was conducted in the medical war… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(48 reference statements)
0
0
0
Order By: Relevance
“…This study found no correlation between sleep quality and gender, planned surgical site, and method of operation. For gender, similar results were obtained by Şen et al [23] and Binte Arman [22]. However, in Terp et al [20], Ünsal et al [24], and Javadi et al [25], female gender was one of the factors determining poor sleep quality.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This study found no correlation between sleep quality and gender, planned surgical site, and method of operation. For gender, similar results were obtained by Şen et al [23] and Binte Arman [22]. However, in Terp et al [20], Ünsal et al [24], and Javadi et al [25], female gender was one of the factors determining poor sleep quality.…”
Section: Discussionsupporting
confidence: 71%
“…It is worth deepening future analyses of PSQI questionnaires in terms of subjective assessment of sleep quality in surgically treated patients. Binte Arman et al [22] proved that patients who had worse sleep quality at home also presented subjectively worse sleep quality in hospital conditions. This study found no correlation between sleep quality and gender, planned surgical site, and method of operation.…”
Section: Discussionmentioning
confidence: 99%